UJI EFEKTIVITAS BEBERAPA MEDIA UNTUK PERBANYAKAN AGENS HAYATI Trichoderma sp. - HS, Gusnawaty; Taufik, Muhammad; Bande, La Ode Santiaji; Asis, Agus (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2017)
Effectiveness test of several media for propagation biological agent Trichoderma sp.. This study aims to look at the effectiveness of some media to propagation of Trichoderma sp. and to determine the effectiveness of the media that has the best propagation of Trichoderma sp. This research is compiled in a completely randomized design (CRD), consists of seven treatment propagation medium that is 1) Media dregs sago (A), 2) Media dregs of the cashew nut shell (B), 3) Media sawdust (C), 4) Media maize (D), 5) Media bran (E ), 6) Media rice (F), 7) Media rice husk (G). The results showed that the medium used for propagation Trichoderma sp. have varying effectiveness. The most effective media for propogation Trichoderma sp. is media bran, with growth capability Trichoderma sp on day 4days after incubation reaches 100%, the difference in weight of the media before and after incubation Trichoderma sp. 2,04 g and the number of conidia 104,125.103/g media.